A fuel-payload ratio based flight-segmentation benchmark. (August 2018) - Kaivanto, Kim; Zhang, Peng
Highlights: We derive the Fuel-Payload Ratio (FPR) for parsimoniously segmenting itineraries. Microeconomic analogue of FPR is Total Variable Input curve with respect to design range. Economically and technically efficient design ranges diverge due to fixed costs on payload. Fuel-saving segmentation thresholds respond ⩾ 0.42:1 to lost-fuel fraction ( λ ) %-increases. Equal-leg-length itineraries are most fuel-efficient. Abstract: Airlines and their customers have an interest in determining fuel- and emissions-minimizing flight segmentation. Starting from Küchemann's Weight Model and the Breguet Range Equation for cruise-fuel consumption, we build an idealized model of optimal flight segmentation for maximizing fuel efficiency and minimizing emissions under the assumption that each leg is operated with an aircraft of segment-length-matching design range. When a multi-leg ( ⩾ 2 ) itinerary is most efficient, legs are ideally of equal length. Instrumental to the parsimony of this flight-segmentation benchmark is a new efficiency metric: Fuel-Payload Ratio (FPR). The FPR approach has a one-to-one correspondence with the standard microeconomic cost-curves framework, which avails the standard tools of microeconomic analysis for cost-efficient design-range determination and optimal flight segmentation. This makes it possible to make direct comparisons between (i) technically efficient design-range and flight-segmentation solutions and (ii) their economically efficient counterparts. Even modest fixed-cost components cause the latter to diverge non-trivially from the former.